2019
DOI: 10.5334/ijic.4642
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Access and Reducing Costs for Glaucoma with Integrated Hospital and Community Care: A Case Study from Australia

Abstract: Introduction:Glaucoma, a chronic eye disease requires regular monitoring and treatment to prevent vision-loss. In Australia, most public ophthalmology departments are overburdened. Community Eye Care is a ‘collaborative’ care model, involving community-based optometrist assessment and ‘virtual review’ by ophthalmologists to manage low-risk patients. C-EYE-C was implemented at one Australian hospital. This study aims to determine whether C-EYE-C improves access to care and better utilises resources, compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…This study also documented the long waiting times, in excess of a year for a hospital appointment and that one‐in‐six patients did not have glaucoma or were discharged from the hospital clinic. This confirms a role for schemes to triage2019 these referrals or referral refinement 2010…”
Section: Discussionmentioning
confidence: 61%
“…This study also documented the long waiting times, in excess of a year for a hospital appointment and that one‐in‐six patients did not have glaucoma or were discharged from the hospital clinic. This confirms a role for schemes to triage2019 these referrals or referral refinement 2010…”
Section: Discussionmentioning
confidence: 61%
“…Several investigations have quantified the clinical examination, test interpretation and the clinical decision-making of optometrists versus ophthalmologists in glaucoma care. 22 27 Substantial agreement between ophthalmologists and optometrists on management decisions has been demonstrated in many of these, 22 27 with higher levels of training being linked with higher agreement between care providers. 25 The results from this scheme align with these findings of good agreement between the optometrists’ clinical examination findings and decisions to return patients non-routinely to the hospital, and the ophthalmologists’ decisions when these patients were seen.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies reporting the benefits of using telemedicine or collaborative care to screen populations for DR, 13 14 and a more recent study has demonstrated that collaborative care models can be used in the Australian setting to assist hospitals to improve efficiencies and reduce costs for existing referral wait lists for low-risk glaucoma. 15 However, there have been relatively few reports to quantify ways in which such collaborative care models would perform for DR.…”
Section: Introductionmentioning
confidence: 99%